Micro-Ribonucleic Acid-216a Regulates Bovine Primary Muscle Cells Proliferation and Differentiation via Targeting SMAD Nuclear Interacting Protein-1 and Smad7 - Yang, Zhaoxin; Song, Chengchuang; Jiang, Rui; Huang, Yongzhen; Lan, Xianyong; Lei, Chuzhao; Chen, Hong (Frontiers in Genetics, 2019)
MicroRNAs (miRNAs), belonging to a class of evolutionarily conserved small noncoding RNA of ~22 nucleotides, are widely involved in skeletal muscle growth and development by regulating gene expression at the post-transcriptional level. Herein, this study was to investigate the function and mechanism of miR-216a during bovine primary muscle cells proliferation and differentiation. During the proliferation and differentiation phases, the expression level of miR-216a both presented a downward trend. In cells proliferation phase, RT-qPCR, western blot, EdU, CCK8 and Flow cytometry experiments showed that overexpression of miR-216a inhibited the expression of proliferation-related genes and reduced the cell proliferation status, leading to cells G1 phase arrest. In cells differentiation stages, RT-qPCR and western blot experiments showed that overexpression of miR-216a suppressed myogenic maker genes mRNA and protein level. Bioinformatics analysis, dual‐luciferase report analysis and experimental verification demonstrated that SNIP1 and smad7 were the directly targets of miR-216a regulating bovine primary muscle cells proliferation and differentiation, respectively. Altogether, these findings found that miR-216a possessed a negative role for the proliferation and differentiation of bovine primary muscle cells via targeting SNIP1 and smad7.